High-Performance Photocatalytic Multifunctional Material Based on Bi4Ti3O12-Supported Ag and Ti3C2Tx for Organic Degradation and Antibacterial Applications - Kexi Zhang; Bingdong Yan; Xiaohong Wang; Yang Cao; Wanjun Hao; Jinchun Tu (Biosensors)
With the rapid development of modern science and technology and the diversification of social needs, traditional single-performance materials struggle to meet the complex and changeable application scenarios. To address the multifaceted requirements of biomedical applications, such as disease diagnosis and treatment, scientists are dedicated to developing new multifunctional biomaterials with multiple activities. Bi4Ti3O12 (BTO), despite its versatility and application potential, has insufficient photocatalytic performance. Silver nanoparticles (Ag) and Ti3C2Tx are particularly effective as antibacterial materials but they have relatively single functions. In this study, BTO/Ag/Ti3C2Tx biomultifunctional materials were constructed by combining BTO with Ag and Ti3C2Tx. We discovered that the addition of Ag and Ti3C2Tx effectively optimized the visible light absorption characteristics of BTO, reduced the electron transfer resistance, and increased the carrier concentration, thus significantly improving the photocatalytic performance of composite material, thereby markedly improving the composite’s photocatalytic performance and its efficacy in photochemical sensing and photodegradation. At the same time, BTO, as a carrier, effectively avoids Ag and Ti3C2Tx agglomeration and gives full play to its antibacterial properties. In the specific performance studies, ascorbic acid and MB were used as the subjects of photochemical sensing and photodegradation properties, while Escherichia coli and Staphylococcus aureus were tested for antibacterial properties. The BTO/Ag/Ti3C2Tx composite showed remarkable results in all assessments, demonstrating its potential as a versatile antibacterial and photocatalytic material.